2015
DOI: 10.46912/napas.6
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Human Blood Groups to Human Immunodeficiency Virus (HIV) and Hepatitis B Virus (HBV) Infections

Abstract: Susceptibility of blood groups to HIV/AIDS and Hepatitis B virus infections in human subjects was studied. One hundred and fifty adult male and female patients who came for routine check up at the Heart to Heart Centre, General Hospital Calabar and the General Hospital Ogoja in Cross River State were used for this investigation.The patients were classified into three groups with group I consisting of sixty (60) normal subjects ( i.e. non HIV/AIDS and non HBV patients) serving as control. Group II was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Twenty‐seven studies were identified from countries with HIV prevalence of more than 1% (higher endemic areas) 15,18–20,22,71–92 and 23 were from countries with HIV prevalence of less than 1% 12–14,16,17,21,93–109 . Within the regions of Africa, Asia and America, there were 26 studies, 15,18–20,22,71–86,88–92 23 studies 12,14,16,17,21,87,93–109 and 1 study, 13 respectively. Thirty‐three studies included participants who were blood donors, 12,13,16–18,20,71–74,76,78,80–82,87,89,91–96,98,99,101–106,108,109 12 from populations of HIV‐infected patients, 14,15,19,75,79,83,84,86,88,97,100,107 and 5 from the general population 21,22,77,85,90 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty‐seven studies were identified from countries with HIV prevalence of more than 1% (higher endemic areas) 15,18–20,22,71–92 and 23 were from countries with HIV prevalence of less than 1% 12–14,16,17,21,93–109 . Within the regions of Africa, Asia and America, there were 26 studies, 15,18–20,22,71–86,88–92 23 studies 12,14,16,17,21,87,93–109 and 1 study, 13 respectively. Thirty‐three studies included participants who were blood donors, 12,13,16–18,20,71–74,76,78,80–82,87,89,91–96,98,99,101–106,108,109 12 from populations of HIV‐infected patients, 14,15,19,75,79,83,84,86,88,97,100,107 and 5 from the general population 21,22,77,85,90 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, with the exception of one study which only differentiated non‐O blood groups from blood group O, 72 all remaining studies described data across all blood groups. Twenty‐seven studies were identified from countries with HIV prevalence of more than 1% (higher endemic areas) 15,18–20,22,71–92 and 23 were from countries with HIV prevalence of less than 1% 12–14,16,17,21,93–109 . Within the regions of Africa, Asia and America, there were 26 studies, 15,18–20,22,71–86,88–92 23 studies 12,14,16,17,21,87,93–109 and 1 study, 13 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations